2021
DOI: 10.3390/nu13030943
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in the First Week after Stroke Is Associated with Discharge to Home

Abstract: Malnutrition is associated with poor clinical outcomes in stroke patients. The effect of early nutritional intake after admission on home discharge is unclear. We evaluated the impact of energy intake in the first week of hospitalization of acute stroke patients on home discharge and activities of daily living (ADL). A retrospective cohort study was conducted with 201 stroke patients admitted to an acute care hospital in Japan. The energy and protein intake during the first week were evaluated. Multivariate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
(76 reference statements)
2
19
0
Order By: Relevance
“…Therefore, it is suggested that a healthy diet may be an effective approach for the prevention of malnutrition and functional disability in older people, especially in those with stroke. A previous study showed that early nutritional intake after acute stroke admission had positive impacts on home discharge and ADL [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that a healthy diet may be an effective approach for the prevention of malnutrition and functional disability in older people, especially in those with stroke. A previous study showed that early nutritional intake after acute stroke admission had positive impacts on home discharge and ADL [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is common in patients with neurological conditions, including stroke. The causes of this abnormality are directly related to neurological diseases, such as cognitive functions and disorder of consciousness, neurogenic vomiting, neurogenic dysphagia, depression, motor deficit and gastrointestinal dysfunction [ 8 , 9 , 10 ].…”
Section: Risk Of Malnutrition After Strokementioning
confidence: 99%
“…It greatly increases the risk of complications such as pressure ulcers and infections (especially of the respiratory system), electrolyte disturbances, coagulation disorders, anemia, osteoporosis and bradycardia and also reduces the quality of life. Furthermore, it influences the hospitalization time and the number of stays in intensive care units and reduces the effectiveness of rehabilitation [ 10 ]. Besides, malnutrition also increases mortality from roughly 30 to 180 days after the ischemic incident.…”
Section: Risk Of Malnutrition After Strokementioning
confidence: 99%
“…People with neurological diseases, including poststroke patients, are particularly prone to malnutrition. That malnutrition is caused by ailments associated with neurological diseases, such as impaired consciousness and cognitive functions, neurogenic dysphagia, neurogenic vomiting, gastrointestinal dysfunction, motor deficits or depression [ 1 , 2 , 3 ]. According to ESPEN (European Society for Clinical Nutrition and Metabolism), malnutrition is defined as “a condition resulting from the lack of intake or absorption of nutrients, leading to a change in body composition, physical and intellectual impairment of the body’s physical and intellectual function, and adversely affecting the treatment of the underlying disease” [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this condition significantly extends hospitalization time, increases the frequency of treatment in intensive care units, and negatively affects the effectiveness of rehabilitation. Reducing the concentration of proteins reduces muscle strength as well as impairs immunity [ 3 ]. Importantly, in a clinical trial FOOD (Feed Or Ordinary Diet, 4023 participants, aged 71 ± 12.5, follow up period 6 months) it has been shown that malnutrition is associated with increased mortality in patients after stroke (odds ratio (OR) 2.32, 95% confidence interval (CI) 1.78–3.02) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%